Sebuah PERLINDUNGAN HUKUM BAGI PENULIS “NOVEL SEMESTA” (ALTERNATIF TERHADAP TINDAKAN PLAGIARISME MELALUI PLATFORM “X” MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014): PERLINDUNGAN HUKUM BAGI PENULIS NOVEL SEMESTA ALTERNATIF - Zahrani, Annisa Putri; Elisabeth Pudyastiwi; Elly Kristiani Purwendah (Academos, 2025)
This research aims to identify the elements of plagiarism, analyze the legal protection for alternative universe novel writers who are victims of plagiarism, and find out the legal consequences for the perpetrators and the application of the law in practice. The method used is normative and empirical juridical with doctrinal legal research specifications. Data is collected through literature studies and online platforms, then analyzed narratively. The results of the study show that plagiarism in AU novels can be seen from the similarity of plot, dialogue, characterization, and story structure. Legal protection is regulated in Article 1 of Law No. 28 of 2014 concerning Copyright, including moral rights and economic rights regulated by Article 5 and Article 9, and the term of copyright protection is regulated by Article 58. The author can file civil and criminal lawsuits in accordance with Article 113 of the UUHC. For digital plagiarism, Law No. 11 of 2008 concerning Electronic Information and Transactions (UUITE) also provides protection regulated in Article 35. In practice, dispute resolution is more often carried out through non-litigation channels such as mediation and negotiation on digital platforms. In addition, publishers play an important role in helping authors protect their copyrights